A Comparative Analysis of Software Development Models Based On Various Parameters - Srivastava, Archana (International Journal of Computer Sciences and Engineering, 2019)
Gradually I.T industry is increasingly relying on a growing quantity of ever-larger software. The fashion of growing technical complexity of the systems united with the requirement for repeatable and predictable process methodologies have driven system developers to establish system development models. With the rising operations of organizations, the need to automate the various activities increased. With this need the concept of system lifecycle models came into survival that emphasized on the need to follow some structured approach towards building new or improved system. At present the software systems cannot be built with mathematical or physical certainty so all software systems are imperfect because they cannot be built with mathematical or physical certainty. The set of processes those proved to be effective and efficient for software development in one organization may or may not be followed in another organization. That is other organization finds another approach for software development more convenient to work with. The software development process is the very complicated thing without any proper step by step generating procedure so to make the software development processes simple and systematic the software development life cycle came in to existence. This is the systematic and structural method of software developing process. The SDLC defines the framework that includes different activities and tasks to be carried out during the software development process. The development lifecycle of software Comprises of four major stages namely Requirement Elicitation, Designing, Coding and Testing. This workflow is a guideline for successful planning, organization and final execution of the software project. There are various software development life cycle models that are used in the software development process heaving their own advantages and disadvantages.